Pushover analysis for cold formed storage rack structures - Kalavagunta S. (Jordan University of Science and Technology, 2023)
This study investigated the progressive collapse of cold formed storage rack structures subjected to seismic loading, using pushover analysis. A simple storage rack cold formed steel structure was analyzed with static, non-linear procedure in accordance with FEMA 356 specifications and progressive collapse recorded such as occupancy, immediate occupancy, life safety and collapse prevention. Pushover analysis was found to be a useful analysis tool for the conventional storage racking systems giving good estimates of the overall displacement demands, base shears and plastic hinge formation. 2012 JUST. All Rights Reserved.